Force Projection in the Time of Scurvy: The Destruction of the 1740-42 West Indies Expedition - Chapman, Craig S. (The Northern Mariner / Le marin du nord, 2023)
The massive British West Indies expedition of 1740-42 during the War of Jenkins’ Ear, launched with an ambitious goal, produced nothing beyond terrible losses. The enormous number of deaths from yellow fever has obscured the true reasons for the defeat at Cartagena de Indias that has often been blamed on the army’s slow siege tactics. The author, following his research for Disaster on the Spanish Main: The Tragic British American Expedition to the West Indies during the War of Jenkins’ Ear, has further developed evidence from British musters that upends common assumptions about yellow fever’s impact and, instead, traces the cause of the expedition’s failure to poor health management and misguided military leadership. L'expédition massive des Antilles britanniques de 1740-1742 pendant la guerre de l'Oreille de Jenkins, lancée avec un objectif ambitieux, n'a rien produit d'autre que de pertes terribles. Le nombre énorme de décès dus à la fièvre jaune obscurcit les véritables raisons de la défaite à Carthagène des Indes, souvent imputée à la lenteur des tactiques de siège de l'armée. L'auteur, suite à ses recherches pour Disaster on the Spanish Main: The Tragic British American Expedition to the West Indies during the War of Jenkins’ Ear, a étudié en profondeur les données probantes issues des registre militaire britanniques pour réfuter les hypothèses courantes sur l'impact de la fièvre jaune et attribuer plutôt l'échec de l'expédition à une mauvaise gestion de la santé et à un leadership militaire peu judicieux.